Intervensi keperawatan berdasarkan teori Becoming a Mother dari Mercer: Sebuah kajian pustaka - Yani, Erna Rahma; Rustina, Yeni; Agustini, Nur; Mudzakkir, Muhammad (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The process of becoming a mother requires mothers to adapt during the transition that occurs immediately after childbirth. Nursing interventions based on Mercer's theory of becoming a mother have been developed in several countries, but their form and scope have not been comprehensively mapped. Purpose: To explore and map the scientific evidence for nursing interventions based on Mercer's theory of becoming a mother. Method: A scoping review was conducted based on Joanna Briggs Institute (JBI) guidelines. Articles were searched in PubMed, Scopus, Proquest, and ScienceDirect databases using a search strategy based on the Population-Concept-Context (PCC) framework. Keywords and synonyms relevant to nursing interventions, the process of becoming a mother, and the postpartum period were identified. A combination of free keywords and standard terms (Medical Subject Headings/MeSH) were used in the search using Boolean operators (AND and OR). Analysis included the population, intervention characteristics, implementation methods, and reported outcomes. Results: Five articles met the inclusion criteria for further analysis. Nursing interventions based on Mercer's theory were generally developed in the form of structured education, training, counseling, and technology-based multimodal approaches. Interventions delivered from the third trimester of pregnancy through the postpartum period have been shown to be effective in improving maternal role adaptation, self-efficacy, and mother-infant bonding. However, the duration of the interventions and study designs varied across the five articles. Conclusion: Nursing interventions based on Mercer's theory effectively support the parenting process by strengthening knowledge, parenting skills, and emotional adjustment. Further studies are needed for standardization and long-term evaluation. Suggestion: In order to improve the quality of nursing services, it is recommended that nurses develop a theory-based standardized nursing intervention model. Keywords: Mothering; Mercer's Theory; Nursing Interventions. Pendahuluan: Proses menjadi ibu memerlukan kemampuan adaptasi maternal pada masa transisi yang terjadi segera setelah melahirkan. Intervensi keperawatan berdasarkan teori Becoming a Mother dari Mercer telah dikembangkan di beberapa negara, namun bentuk dan cakupannya belum dipetakan secara komprehensif. Tujuan: Untuk mengeksplorasi dan memetakan bukti ilmiah dari intervensi keperawatan berdasarkan teori Becoming a Mother dari Mercer. Metode: Scoping review dilakukan dengan berpedoman pada Joanna Briggs Institute (JBI). Pencarian artikel dilakukan pada basis data PubMed, Scopus, Proquest, dan ScienceDirect dengan strategi pencarian berdasarkan kerangka Populasi-Concept-Context (PCC) dengan mengidentifikasi istilah utama dan sinonim yang relevan dengan intervensi keperawatan, proses menjadi ibu (becoming a mother), serta periode postpartum. Kombinasi kata kunci bebas dan istilah baku (Medical Subject Headings/MeSH) digunakan dalam pencarian dengan operator Boolean (AND dan OR). Analisis mencakup populasi, karakteristik intervensi, metode implementasi, dan luaran yang dilaporkan. Hasil: Didapatkan lima artikel memenuhi kriteria inklusi untuk dianalisis lebih lanjut. Intervensi keperawatan berdasarkan teori Mercer umumnya dikembangkan dalam bentuk edukasi terstruktur, pelatihan, konseling, dan pendekatan multimodal berbasis teknologi. Intervensi yang diberikan sejak trimester ketiga kehamilan hingga periode postpartum menunjukkan efektifitas dalam emningkatkan adaptasi peran maternal, efikasi diri, serta ikatan ibu dan bayi. Namun durasi intervensi dan desain penelitian menunjukkan variasi pada kelima artikel. Simpulan: Intervensi keperawatan berbasis teori Mercer efektif mendukung proses menjadi ibu melalui penguatan pada aspek pengetahuan, kemampuan pengasuhan, dan penyelarasan emosional. Studi lanjutan diperlukan untuk standardisasi dan evaluasi jangka panjang. Saran: Guna meningkatkan kualitas layanan keperawatan, disarankan perawat mengembangkan model intervensi keperawatan terstandar berbasis teori. Kata Kunci: Becoming a Mother; Intervensi Keperawatan; Teori Mercer.